Analisis Pelaksanaan Akad Ijarah Muntahiyah Bit Tamlik Di Lembaga Pembiayaan Syariah Di Indonesia - Mardiyah, Suci; Khairi, Rifqil (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
The purpose of this article is to analyze the implementation of the Ijarah Muntahiyah bi al-tamlik (IMBT) agreement in the practice of sharia financing institutions in Indonesia. The method used is a literature study by examining aspects of contract structure, determining rental prices and purchase options, as well as the roles and responsibilities of the parties in IMBT practice. IMBT is a hybrid contract that combines rental transactions (ijarah) and buying and selling (bai'). In practice, IMBT provides flexibility for customers to obtain ownership of leased assets according to their financial capabilities. However, the structure of the IMBT contract must be carried out carefully so that it complies with sharia principles. Determination of rental prices and purchase options must also be carried out fairly and transparently to maintain a balanced bargaining position between Islamic financial institutions and customers. In addition, the roles and responsibilities of each party need to be clearly regulated, especially regarding asset maintenance, profit sharing, and transfer of asset ownership at the end of the lease term. By understanding these aspects, it is hoped that the implementation of IMBT contracts by sharia financial institutions in Indonesia can provide optimal benefits for customers and be in line with sharia principles.